1983
DOI: 10.1007/bf00216197
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical evidence of intragranular acetylation of ?-MSH in the melanotrophic cells of the rabbit

Abstract: Melanotrophic cells of the pars intermedia of the rabbit were studied at the electron-microscopic level by means of the immuno-gold technique with the use of antisera against gamma 3-MSH and alpha-MSH. Both antibodies labelled all secretory vesicles stored in the peripheral cytoplasm, but secretory vesicles and intrasaccular condensations in the Golgi area reacting for gamma 3-MSH were not labelled with the antibody against alpha-MSH. Since this antibody appears to recognise only the acetylated form of alpha-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Since the axonal transport of the neurohypophysial peptides occurs exclu sively within neurosecretory vesicles, these data strongly in dicated that the neurosecretory vesicles contained the me chanisms for post-translational processing of precursors. Further experimental work supporting this view of the role of secretory vesicles in precursor processing can be found in various studies of proinsulin [21,22,47,80,91] and POMC [31,36,58,93] processing. In some cases (e.g., for parathyroid hormone processing [38], the interpretation is that precursor processing can occur in the Golgi complex.…”
Section: The Secretory Vesicle Hypothesismentioning
confidence: 76%
“…Since the axonal transport of the neurohypophysial peptides occurs exclu sively within neurosecretory vesicles, these data strongly in dicated that the neurosecretory vesicles contained the me chanisms for post-translational processing of precursors. Further experimental work supporting this view of the role of secretory vesicles in precursor processing can be found in various studies of proinsulin [21,22,47,80,91] and POMC [31,36,58,93] processing. In some cases (e.g., for parathyroid hormone processing [38], the interpretation is that precursor processing can occur in the Golgi complex.…”
Section: The Secretory Vesicle Hypothesismentioning
confidence: 76%
“…Immunohistochemical studies showed a co-localized distribution of two or more of the POMC-derived peptides in the same corticotropic and melanotropic cells of the anterior and intermediate lobe of the pituitary, and in the POMC neurons in the basal hypothalamus, at the light and electron microscopical level (Akil et al, 1978;Bloch et al, 1978Bloch et al, , 1979Crine et al, 1978;Dub6 et al, 1978;Sofroniew, 1979;Weber et al, 1979;Chatelain et al. 1979;Nilaver et al, 1979;Vaudri et al, 1980;Guy et al, 1980;Loh et al, 1982;Cantin et al, 1983;Stoeckel et al, 1983Stoeckel et al, , 1985Mains et al, 1983;Tanaka and Kurosumi, 1986;Powel and Baker, 1987;Kantin et al, 1988). Pelletier and Leclerc (1979) have shown at the ultrastructural level that ACTH is present in dense-core secretory granules in the brain.…”
Section: Co-localization Of Pomc Derived Peptidesmentioning
confidence: 99%